Optimized Sleep After Brain Injury (OSABI): A Pilot Study of a Sleep Hygiene Intervention for Individuals With Moderate to Severe Traumatic Brain Injury. (February 2020) - Makley, Michael J.; Gerber, Don; Newman, Jody K.; Philippus, Angie; Monden, Kimberley R.; Biggs, Jennifer; Spier, Eric; Tarwater, Patrick; Weintraub, Alan
Background . Disrupted sleep is common after traumatic brain injury (TBI) particularly in the inpatient rehabilitation setting where it may affect participation in therapy and outcomes. Treatment of sleep disruption in this setting is varied and largely unexamined. Objective . To study the feasibility of instituting a sleep hygiene intervention on a rehabilitation unit. Methods . Twenty-two individuals admitted to a brain injury unit were enrolled and allocated, using minimization, to either a sleep hygiene protocol (SHP) or standard of care (SOC). All participants wore actigraphs, underwent serial cognitive testing, and had light monitors placed in their hospital rooms for 4 weeks. Additionally, participants in the SHP received 30 minutes of blue-light therapy each morning, had restricted caffeine intake after noon, and were limited to 30-minute naps during the day. SHP participants had their lights out time set according to preinjury sleep time preference. Both groups were treated with the same restricted formulary of centrally acting medications. Results . Of 258 patients screened, 27 met all study inclusion criteria of whom 22 were enrolled. Nine participants in each group who had at least 21 days of treatment were retained for analysis. The protocol was rated favorably by participants, families, and staff. Actigraph sleep metrics improved in both groups during the 4-week intervention; however, only in the SHP was the change significant. Conclusions . Sleep hygiene is a feasible, nonpharmacologic intervention to treat disrupted sleep in a TBI inpatient rehabilitation setting. A larger study is warranted to examine treatment efficacy.ClinicalTrials.gov Identifier: NCT02838082.